2016
DOI: 10.1017/s1751731115002499
|View full text |Cite
|
Sign up to set email alerts
|

Determining optimum age of Holstein dairy calves when adding chopped alfalfa hay to meal starter diets based on measures of growth and performance

Abstract: The present study was conducted to determine the optimum age of Holstein dairy calves for an effective inclusion of alfalfa hay (AH) in starter feed on performance, apparent digestibility and feeding behavior. A total of 40 Holstein dairy calves (20 female and 20 male) were used in a completely randomized design in which calves were randomly assigned to one of four different dietary treatments including control (CON) calves fed starter feed without any forage and three treatments consisting of the same starter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 34 publications
4
30
1
Order By: Relevance
“…However, some evidence does suggest that meal patterns acquired in early life may persist (Miller-Cushon and DeVries, 2015), such that encouraging a developing pattern of frequent, small meals may be beneficial. Introducing forage early in the pre-weaning stage, as opposed to closer to weaning, has also been found to enhance positive effects associated with forage intake, increasing time spent consuming starter as well as rumination time (Hosseini et al, 2016).…”
Section: Behaviormentioning
confidence: 99%
“…However, some evidence does suggest that meal patterns acquired in early life may persist (Miller-Cushon and DeVries, 2015), such that encouraging a developing pattern of frequent, small meals may be beneficial. Introducing forage early in the pre-weaning stage, as opposed to closer to weaning, has also been found to enhance positive effects associated with forage intake, increasing time spent consuming starter as well as rumination time (Hosseini et al, 2016).…”
Section: Behaviormentioning
confidence: 99%
“…The potential effect of dietary forage supplementation on the performance and rumen development in dairy calves is well established (Jahani‐Moghadam et al., ; Mirzaei et al., ). Provision of forage to young calves has been recommended because it has been shown to increase starter intake, average daily gain (ADG), as well as improve rumen fermentation (Jahani‐Moghadam et al., ; Mirzaei et al., ), stimulate the muscular layer of the rumen (Suárez et al., ; Beiranvand et al., ; Mirzaei et al., ), promote rumination (Hosseini et al., ; EbnAli et al., ) and reduce behavioural problems (Phillips, ). Recently, Hosseini et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hosseini et al. () reported that the inclusion of chopped alfalfa hay (AH) at the rate of 15% to the starter diet when calves were 2 weeks old, as compared with CON (no added AH), resulted in producing heavier calves with greater starter intake and better ADG through pre‐ and post‐weaning periods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference might be explained by the inclusion of alfalfa (3.1% starter DM) in starter diet in the study of Laarman et al (2012). Forage can stimulate starter DMI and act as a buffer when calves consume high starch levels from starter grains (Castells et al, 2012;Montoro et al, 2013;Hosseini et al, 2016).…”
Section: Discussionmentioning
confidence: 99%